Rhymed and traditional audio description according to the blind and partially sighted audience: Results of a pilot study on creative audio description - Zabrocka, Monika (The Journal of Specialised Translation, 2018)
The study described in this article is based on rhymed and traditional AD prepared for the animated film Boundin’ (Pixar, 2003). The cartoon with two kinds of AD was presented to blind audiences, both children and adults. Next, the audience was asked questions about the plot, the characters and some technical aspects of AD, including its general character, the vocabulary used and the narrator’s voice. The aim of the study was to verify whether artistic AD is able to provide all the information necessary for the blind to understand the film on an equal level with the sighted. In addition, the study examines how attractive artistic AD can be to blind or partially sighted viewers and whether it is a source of additional aesthetic experience for them. It also considers artistic AD as an acceptable alternative to traditional AD, and helps to assess who accepts such an AD better: blind or partially sighted, children or adults.